EFEKTIFITAS FERMENTASI GULA SEBAGAI ATRAKTAN NYAMUK - alfi kurniati; indra chahaya; nurmaini * (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT The impact of mosquitoes and mosquito repellent can cause health hazards to humans, as well as the expensive of mosquito trap is a problem at this time. The purpose of study on the fermentation of sugar as a mosquito attractant is to determine whether there is any difference in the number of mosquitoes trapped by the fermentation of sugar concentration variation and long of observation. This research was conducted at the center for Environmental health Engineering field. This study is quasi-experimental, and the method used is Completely Randomized Factorial Design (RAL) The first factor is fermented of sugar concentration which are; 0%, 5%, 15%, 25%, and 35%. The second factor is long observation on day-1, day-2, day-3, day-4, day-5, and day-6. This study was conducted from March until June 2015.. The sample used in this study is 300 adult mosquitoes for each treatment. Data were analyzed using Kruskal Wallis Statistical test and continued Duncan test. The result showed that there is a difference of five variations fermentation of sugar concentration on the number of mosquitoes trapped. There is no difference in the number of mosquitoes trapped with long observations. Fermentation of sugar concentration in 35% indicates as the effective concentration because there is a significant difference from five other variations of the fermentation of sugar concentration. The higher sugar material, the stronger the adhesion of the fermentation of sugar. Long observation of the number of mosquitoes trapped showed that there is no significant difference from day to day-2 until day-5, and start decline at day-6. Fermentation of sugar can be used as an alternative for vector control especially the mosquito as the safe attractant for the environment and humans. The fermented sugar as a mosquito attractant should be used more than one in a room.